Evaluation of [18F]PSMA-1007 uptake variability in patients with prostate cancer - Trägårdh, Elin ; 0000-0002-7116-303X; Larsson, Måns; Minarik, David; Enqvist, Olof; Edenbrandt, Lars (Clinical Physiology and Functional Imaging, 2025)
Background: The biodistribution of PSMA-ligands is of interest in radionuclide therapy planning. We investigated the variability of [18F]PSMA-1007 uptake in organs at risk and in relation to tumour burden in prostate cancer patients. Methods: A total of 1086 patients who underwent PSMA PET-CT for staging or recurrence of prostate cancer were included. Total lesion volume (TLV) and total lesion uptake (TLU) were calculated from manual segmentations. The mean standardized uptake value (SUVmean) in the organs at risk kidneys, liver, parotid glands and spleen was obtained. Correlations between TLV/TLU and SUVmean in normal tissues were calculated using Spearman rank correlation. SUVmean in normal tissues was stratified into groups based on TLV. Results: The median (IQR) SUVmean of the kidneys, liver, parotid glands, and spleen was 13.1 (IQR 4.6), 11.8 (4.4), 18.6 (6.8) and 11.3 (5.8), respectively. The median TLV was 3.8 cm3 (9.7) and median TLU was 31.2 cm3 (106.3). There was no significant correlation between TLV or TLU and SUVmean for the liver, parotid glands, or spleen, but a weak negative correlation between TLV/TLU and SUVmean in the kidneys (r = −0.011, p = 0.0005; r = −0.09, p = 0.003). There was a tendency towards a lower SUVmean in the kidneys and parotid glands in patients with a very high TLV. Conclusions: There was a large uptake variability in organs at risk, which demonstrates the need for individual pretherapy dosimetry. There may be a tumour sink effect in the kidneys and parotid glands in patients with a very high TLV.
Publisher Copyright: © 2025 The Author(s). Clinical Physiology and Functional Imaging published by John Wiley & Sons Ltd on behalf of Scandinavian Society of Clinical Physiology and Nuclear Medicine.
Keywords: PET, tumour sink effect; prostate cancer; PSMA; radioligand therapy; [18F]PSMA−1007